Present status of broodstock management at carp hatcheries in Jessore - Samad, MA; Hossain, MT; Rahman, BMS (Journal of the Bangladesh Agricultural University, 2014)
This study represented a survey report on present status of management of carp brood fish. The survey was conducted with 40 hatcheries at Chacrha in Jessore from June to November, 2012. Production of brood fish was found to depend on the combined interaction between feed and culture technique. Some information showed that brood fish selection for induced breeding was done on the basis of their experience. Pond preparation was carried out properly but stocking density of brood fish was quite high and water quality was not maintained properly. Negative selection of brood fish was done in few hatcheries aiming at reducing the cost for collecting or purchasing good quality broods. The sources of brood fish were mainly own and other sources were Halda River, Padma River, Govertment brood bank and World Fish Center. Feed used for brood carp fish were mainly rice bran (34.57%), mustard oil cake (21.78%), vitamin and mineral premix (0.8%), wheat flour (8.64%), fish meal (8.64%) and soya bean flour (10.37%), maize flour (6.91%), rice ( 6.91%), di-calcium (1.73%), salt (0.34%) and antioxidant (0.04%) . Nutritional composition of feed was mainly crude protein (30-40%), crude lipid (10-12%), carbohydrate (20-30%). Protein percentage of feed always tried to keep 26% even though it was varied due to the other feed ingredients. Fertilizer such as Triple super phosphate (0.73 kg/dec), urea (0.25 kg/dec), potash (1.5 kg/decl), cowdung (5.19 kg/dec), poultry offal (1.9 kg/dec) and Murite of potash (0.13 kg/dec) were used. Scientific brood and hatchery management could be a good approach to attain the main purpose of aquaculture. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19939 J. Bangladesh Agril. Univ. 11(2): 349-358, 2013